How do we legislate for improved community development? - James M. Otto (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
A large mining project has the potential to be a partner in assisting local communities in their development efforts. Communities located in close proximity to a large mine have every right to expect that the project will benefit their community. Often, reality falls short of their expectations and a hostile environment can result. The use of a contract between a miner and neighbouring communities can be a valuable tool to achieve community development and to help define and manage expectations. This paper introduces the principal issues involved in legislating requirements for community development agreements and also contains model mining act provisions and regulations.
Keywords: O13; Q32; Q34; Q38; 330; community development agreement; mining; mining law; mining regulations; sustainable development